Impact of Leadership Style on Employee Performance (A Case Study on a Private Organization in Iraq) (Texas Journal of Multidisciplinary Studies, 2022)
The purpose of this study is to identify the impact of leadership style on employee performance. A sample size of 100 was used from one private organization in Selangor, Malaysia using convenience sampling technique. The study used quantitative approaches, and a questionnaire was designed. A five-point Likert scale questionnaire was used to determine the impact of leadership style on employee performance. SPSS software was used in analysing the questionnaires. Demographic analysis, normality test, reliability test (Cronbach’s Alpha), descriptive analysis and regression analysis were presented. Descriptive statistics show that the most significant value associated with employee performance is democratic leadership style followed by laissez-faire leadership style and autocratic leadership style. Democratic leadership style has the highest mean value corresponding to 3.783 and standard deviation value of 0.8123, laissez-faire leadership style scores the second highest mean value corresponding to 3.415 and standard deviation value of 0.5855, and autocratic leadership style has the lowest mean value corresponding to 3.403 and standard deviation value of 0.7331 indicating that autocratic leadership style is poorly correlated with employee performance. Regression coefficient analysis shows that there is a significant and positive impact of democratic and laissez-faire leadership styles on employee performance. Autocratic leadership style beta coefficient value is -0.167 with a significant value of 0.025 which is higher than 0.01, hence autocratic leadership is found to have a negative significant impact on employee performance.